Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo - Ng, Heok Hee (Zootaxa, 2004)
Kryptopterus platypogon, a new species of silurid catfish is described from the Rajang River drainage in northern Borneo. Kryptopterus platypogon, together with K. hexapterus and K. cheveyi, can be distinguished from congeners by a combination of the absence of the dorsal fin, a stronglyarched dorsal profile with a pronounced nuchal concavity and palatal teeth in a single elliptical patch. Kryptopterus platypogon differs from K. hexapterus in having a more strongly-projecting lower jaw, larger eye (14.1% HL vs. 8.0 12.6), longer maxillary (135.6% HL vs. 40.0 120.4) and mandibular (119.3% HL vs. 32.3 80.0) barbels that are flattened and ribbon-like (vs. flattened, but ovoid in cross section), and more ventrally-placed eyes (about one quarter of the orbital margin visible when the head is viewed ventrally vs. orbital margin barely visible), and from K. cheveyi in having a strongly projecting lower jaw (vs. upper and lower jaws of equal length), more anal-fin rays (83 vs. 66 71), narrower head (8.6% SL vs. 9.7 12.3) and smaller eye (14.1% HL vs. 18.9 22.7).